Recovery of Copper and Magnetite from Copper Slag Using Concentrated Solar Power (CSP) - Daniel Fernández-González (Metals, 2021)
On the one hand, copper slag is nowadays a waste in copper pyrometallurgy despite the significant quantities of iron (>40 wt. %) and copper (1 to 2 wt. %). On the other hand, solar energy, when properly concentrated, offers great potential in high-temperature processes. Therefore, concentrated solar power (CSP) could be used in the treatment of copper slag to transform fayalite into magnetite and copper sulfides and oxides into copper nodules. This is the objective of this paper. The results show that fayalite was partially decomposed into magnetite and silica. Moreover, copper nodules (65–85 wt. % Cu) were identified in the treated samples, while the initial slag, analyzed by X-ray diffraction, X-ray fluorescence, and SEM-EDX, did not show the presence of metallic copper. Finally, the treated copper slag was crushed and grinded down to 40 μm, and two fractions were obtained by magnetic separation. The magnetic fraction (85%) was mainly comprised of magnetite, while the non-magnetic fraction (15%) had 5–10 wt. % Cu. Considering the experimental results, 7.5–18 kg Cu/t slag might be recovered from the slag. A preliminary economic analysis, considering the current copper price, indicates that only the recovery of copper could represent a significant economic benefit (>30 €/t slag). Therefore, CSP might be a potential candidate for the treatment of copper slag to recover copper and iron.